Attitudes Toward Psychiatry Among Medical Students With a Psychiatric Major at Chongqing Medical University - Li, Xiao; Ai, Ming; Chen, Xiaolu; Gan, Yao; He, Jinglan; Tian, Yu; Zhai, Jian; Yang, Haoling; Kuang, Li (Frontiers in Psychiatry, 2022)
Objectives: To understand the attitudes of medical students with psychiatry major towards psychiatry at Chongqing medical university in China and to find out factors influencing students’ career choice. Methods: The present study used an online web survey tool to assess the attitudes towards psychiatry amongst 422 students majoring in psychiatry at Chongqing medical university in China using sociodemographic and Attitudes Toward Psychiatry-30 items (ATP-30) scales. Descriptive statistics and logistic regression analysis were used to examine associated factors. Results: Three hundred and sixty-nine students (87%) answered the questionnaire. Nearly 54.5% of participants had overall positive attitudes to psychiatry and 80.8% thought psychiatrist can be the career choice. 5.1% showed that they did not want to be a psychiatrist while the left 14.1% were not decisive, the first and fifth year students showed lower desire to be a psychiatrist (74.3% and 69.8%, respectively), the highest percentage recorded is of the third year (90.6%), the female gender, in contact with patients suffering from mental illness, is willing to study psychiatry as a master degree and see good prospects of the psychiatry are positive factors to choose psychiatrist as a career. Conclusions: Students generally have good expectations towards psychiatry, but different opinions are also apprehended and still faced against various challenges to order to provide more psychiatrists.